2020
DOI: 10.1111/jfb.14250
|View full text |Cite
|
Sign up to set email alerts
|

Induced spawning and embryonic and early larval development of bonefish (Albula vulpes)

Abstract: Bonefish (Albula vulpes L.) are a highly prized sport fish. Despite their economic importance, populations in the Florida Keys and Caribbean are in decline, with the early life history undescribed. Injections of carp pituitary extract into A. vulpes during the advanced stages of ovarian development induced ovulation and spawning. Embryos were sampled hourly until hatching into undeveloped, yolk‐sac leptocephalus larvae. These larvae survived 56 h post‐hatch, when myomeres and eyes were developing but not the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Initial rapid larval growth rates (from 4 to 75 hph) in this study were similar to those previously observed in bonefish leptocephali (Halstead et al, 2020) and leptocephali of eels (Miller, 2009). The increase in HC proportions during this period, which are produced by the hydrolysis of simple and complex lipids, could be due to an increase in energy demand by the larvae.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Initial rapid larval growth rates (from 4 to 75 hph) in this study were similar to those previously observed in bonefish leptocephali (Halstead et al, 2020) and leptocephali of eels (Miller, 2009). The increase in HC proportions during this period, which are produced by the hydrolysis of simple and complex lipids, could be due to an increase in energy demand by the larvae.…”
Section: Discussionsupporting
confidence: 91%
“…Until recently, the only elopomorph fishes successfully bred in captivity that would enable analysis of the impact of broodstock nutrition on larval development are several species of anguilliform eels (Mochioka et al, 1993; Tanaka, 2015; Tanaka et al, 2003). Newly developed methods to induce spawning in wild‐caught bonefish (Halstead et al, 2020; Mejri et al, 2019a; Mejri et al, 2020) offer the opportunity to describe the nutritional composition of early larvae, providing a basis for production and growth of larvae under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts by our group led to inducing spawning in wild-caught, pre-spawning aggregation bonefish for the first time (Halstead et al, 2020;Mejri et al, 2019), as well as successful spawning of captive bonefish. However, the larvae from the spawning of wild fish and captive fish did not live past 10 days, indicating nutritional deficiencies and subsequent developmental difficulties (Wills, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about bonefish leptocephalus biology and behavior throughout the pelagic duration of their development. While captively reared bonefish leptocephali displayed a vertical orientation and sporadic short burst swimming motions [ 77 ], these observations were only during the first < 10 days of the 71-day larval period, so volitional swimming behavior throughout development is not understood well enough to inform parameterization. Although burst and critical swimming velocities of other Elopomorph leptocephali have been experimentally measured and could be used in proxy, the ecology governing sustained swimming behavior throughout ontogeny is still not known [ 78 ].…”
Section: Methodsmentioning
confidence: 99%